Boosted electrochemical performance of LiNi0.5Mn1.5O4 via synergistic modification of Li+-Conductive Li2ZrO3 coating layer and superficial Zr-doping. (20th May 2020) - Zhang, Jianning; Sun, Gang; Han, Yi; Yu, Fuda; Qin, Xiujuan; Shao, Guangjie; Wang, Zhenbo
Abstract: Spinel LiNi0.5 Mn1.5 O4 (LNMO) is a competitive cathode material for the next generation high energy density lithium ion batteries (LIBs) because of its high potential (4.7 V) and acceptable theoretical capacity (146.7 mAh g −1 ). Nevertheless, it suffers from severe capacity decay during cycling, especially at elevated temperatures. Herein, we propose an integrated modification strategy combing Li + -conductive Li2 ZrO3 coating layer with superficial Zr-doping. The coating layer of Li2 ZrO3 avoids the direct contact between the cathode material and electrolyte, and favors Li + transport kinetics and interface stability, superficial Zr-doping can greatly improve electron conductivity by inducing an appropriate amount of Mn 3+ . Electrochemical measurements demonstrate that desirable capacity retention of 82.4% can be obtained for 2 wt% Li2 ZrO3 -surface modified LNMO at 25 °C for 5 C rate after 1000 cycles, significantly higher than that of 66.1% for the pristine sample. Notably, the capacity retention of 2 wt% Li2 ZrO3 -coated LNMO sample can maintain up to 83.5% at 1 C rate after 200 cycles at 55 °C. This integrated modification strategy of synergistic coating and doping is regarded as a promising and useful choice for elevating the performance of LIBs.